Neuronal gamma oscillations and activity-dependent potassium transients remain regular after depletion of microglia in postnatal cortex tissue - Lewen, Andrea; Ta, Thuy-Truc; Chausse de Freitas, Bruno; Kann, Oliver (Journal of neuroscience research, 2020)
Microglial cells (resident macrophages) feature rapid activation in CNS disease and can acquire multiple phenotypes exerting neuroprotection or neurotoxicity. The functional impact of surveying (“resting”) microglia on neural excitability and neurotransmission in physiology is widely unknown, however. We addressed this issue in male rat hippocampal slice cultures (in situ) by pharmacological microglial ablation within days and by characterizing neuronal gamma-band oscillations (30-70 Hz) that are highly sensitive to neuromodulators and disturbances in ion and energy regulation. Gamma oscillations support action potential timing and synaptic plasticity, associate with higher brain functions like perception and memory, and require precise communication between excitatory pyramidal cells and inhibitory (GABAergic) interneurons. The slice cultures featured well-preserved hippocampal cytoarchitecture and parvalbumin-positive interneuron networks, microglia with ramified morphology, and low basal levels of IL-6, TNF-α, and nitric oxide (NO). Stimulation of slice cultures with the pro-inflammatory cytokine IFN-γ or bacterial LPS serving as positive controls for microglial reactivity induced MHC-II expression and increased cytokine and NO release. Chronic exposure of slice cultures to liposome-encapsulated clodronate reduced the microglial cell population by about 96%, whereas neuronal structures, astrocyte GFAP expression, and basal levels of cytokines and NO were unchanged. Notably, the properties of gamma oscillations reflecting frequency, number and synchronization of synapse activity were regular after microglial depletion. Also, electrical stimulus-induced transients of the extracellular potassium concentration ([K+]o) reflecting cellular K+ efflux, clearance and buffering were unchanged. This suggests that nonreactive microglia are dispensable for neuronal homeostasis and neuromodulation underlying network signaling and rhythm generation in cortical tissue.
Gesehen am 30.10.2020